Graphene‐based multimode inspired frequency reconfigurable user terminal antenna for satellite communication. Issue 1 (30th November 2017) - Kumar, Jayendra; Basu, Banani; A. Talukdar, Fazal; Nandi, Arnab
Abstract : This study proposes a graphene conductive ink printed textile‐based microstrip antenna capable of switching between S‐band (3.03 GHz, TM 10 mode) and C‐band (5.17 GHz, TM 02 mode and 6.13 GHz, TM 20 mode). The graphene conductive ink printed textile shows surface resistance of 2.7 Ω Sq . − 1, conductivity of 0.37 × 10 5 Sm − 1 and excellent microstructural characteristics, which makes it suitable to be used as a metal sheet to fabricate the antenna structure. To overcome the low‐conductivity issue of graphene conductive ink, a multilayered substrate approach is utilised to improve radiation performances of the antenna. A peak realised gain of 2.09 dBi and radiation efficiency of 74% is achieved at the dominant mode (3.03 GHz). The frequency reconfigurability is introduced by exciting the higher order modes, TM 02 and TM 20 through two different feeding locations. The excitation of ports is controlled through a radio frequency (RF) pin diode switch integrated microstrip transmission line. Subsequently, the proposed structure is further designed using copper foil of thickness ( 17 μ m ) and a comparative analysis of graphene‐based and copper‐based antennas is presented. The proposed antenna performs substantially well in terms of peak realised gain and radiation efficiency compared with that of the existing graphene‐based antenna and the performance deviation with respect to the copper based antenna is lowered significantly.